2022
DOI: 10.1186/s12916-022-02536-5
|View full text |Cite
|
Sign up to set email alerts
|

The duration of protection against clinical malaria provided by the combination of seasonal RTS,S/AS01E vaccination and seasonal malaria chemoprevention versus either intervention given alone

Abstract: Background A recent trial of 5920 children in Burkina Faso and Mali showed that the combination of seasonal vaccination with the RTS,S/AS01E malaria vaccine (primary series and two seasonal boosters) and seasonal malaria chemoprevention (four monthly cycles per year) was markedly more effective than either intervention given alone in preventing clinical malaria, severe malaria, and deaths from malaria. Methods In order to help optimise the timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that the effectiveness of SMC was highest in the rst 28 days after administration, 12,34 which was short duration but slightly longer than that observed here. The shorter duration observed, compared to that previously documented in RCT, 35 may indicate that the period of protection could be even shorter at the population level in areas with gaps in coverage. Furthermore, this may signal a growing resistance to SP, as shorter duration of protection of chemoprophylaxis has been previously associated with increasing resistance.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have shown that the effectiveness of SMC was highest in the rst 28 days after administration, 12,34 which was short duration but slightly longer than that observed here. The shorter duration observed, compared to that previously documented in RCT, 35 may indicate that the period of protection could be even shorter at the population level in areas with gaps in coverage. Furthermore, this may signal a growing resistance to SP, as shorter duration of protection of chemoprophylaxis has been previously associated with increasing resistance.…”
Section: Discussionmentioning
confidence: 50%
“…Current operational plans for high malaria burden countries, including Madagascar ( 45 ), recommend implementing or expanding interventions using anti-malaria drugs to reduce burden in targeted populations, as a supplement to existing base activities (i.e., bednet distribution). Approaches use the regular administration of either a standard first-line antimalarial with a short half-life (protective against reinfection for 13-15 days ( 46 )) to clear existing infections (mass drug administration, MDA, or mass testing and treatment, MTaT) or a longer lasting antimalarial (protective for 21-42 days ( 47, 48 )) to also prevent new infections (seasonal or perennial malaria chemoprophylaxis, SMC, PMC, or intermittent preventive treatment of malaria in pregnancy, IPTp) (see Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, seasonal administration of RTS,S plus SMC improves upon the efficacy of either alone by almost 60% [47 && ]. A sub-study from this trial did note that RTS,S efficacy in this setting declined rapidly after six months, highlighting the importance of correctly timing interventions for the malaria season [48].…”
Section: Malaria Vaccinesmentioning
confidence: 90%